2000
DOI: 10.1207/s15327914nc381_13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical and Oral Vitamin E on Pigmentation and Skin Cancer Induced by Ultraviolet Irradiation in Skh:2 Hairless Mice

Abstract: This study investigates whether supplementation with topical RRR-alpha-tocopherol (Eol), topical RRR-alpha-tocopheryl succinate, and oral RRR-alpha-tocopheryl acetate can reduce the incidence of acute and chronic damage to the skin (i.e., sunburn and pigmentation and skin cancer, respectively) induced by ultraviolet (UV) irradiation to mice. Groups of twenty Skh:2 female hairless pigmented mice were treated with 1) lotion vehicle, 2) 5% Eol lotion, 3) 5% topical RRR-alpha-tocopheryl succinate lotion, or 4) lot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 34 publications
0
71
0
3
Order By: Relevance
“…Topical preparations containing selenium sulfide are frequently used to manage tinea versicolor, seborrheic dermatitis, and dandruff [41,42] . It is commonly incorporated into shampoo for treating dandruff.…”
Section: Discussionmentioning
confidence: 99%
“…Topical preparations containing selenium sulfide are frequently used to manage tinea versicolor, seborrheic dermatitis, and dandruff [41,42] . It is commonly incorporated into shampoo for treating dandruff.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports of ␣ -tocopherol protecting the skin against damage produced by oxidative stresses from UVB ( 24 , 25 ), ␣ -tocopherol levels in the skin decreasing after UV irradiation ( 6 ) or topical application of vitamin E being more useful in comparison with oral ingestion ( 26 ). On the other hand, a review by Sies and Stahl ( 27 ) showed that while nutritional protection against skin damage from sunlight is provided by carotenoids, tocopherols, ascorbate, flavonids, or n -3 fatty acids, the effects of tocopherols in human dietary photoprotection were slight.…”
Section: Discussionmentioning
confidence: 99%
“…It is also effective in some skin conditions resulting from both acute and chronic UV exposure, such as wrinkles [ 24 ] and skin cancers [ 25 ] . Topical combination with vitamin C enhances its antioxidant and photoprotective effects, as well as its stability [ 3 ] .…”
Section: E Vitaminsmentioning
confidence: 99%